Git going with LEGO - Jamene Brooks-Kieffer; Tami Albin (University of Huddersfield Press, 2022)
Git, an open source version control software, is difficult to both teach and learn because it conceals its work in a hidden directory and is often deployed using a command line interface. Yet, version control is an essential tool of reproducible research. Two librarians formed a playful partnership to experiment with teaching Git using LEGO, an approach inspired by our Carpentries Instructor certifications and one's LEGO Serious Play certification. Our method combines novice-centric Carpentries pedagogy with theories of play, constructionism, constructivism, conceptual metaphor, and the hand-mind connection that are foundational to LEGO Serious Play. We share details of developing, testing, and assessing this Git-LEGO combination. Our preliminary study indicates that our LEGO activity may increase learners' short-term retention of Git commands. We discuss future directions for our research and our experiences as academic librarians in a playful partnership.